Innovation in the Use of Interactive Media to Increase Students Interest and Numeracy Literacy Ability - Yuni Ramdhani; Muammar Khadafie (Manunggal Halim Jaya, 2026)
This study aims to analyze the impact of innovations in the use of interactive media on increasing students' interest in learning and numeracy literacy skills at SD Negeri Kokarlian. The background of this research is based on the low involvement of students in conventional numeracy learning, which tends to be monotonous and less contextual. Through a descriptive qualitative approach, data is collected using observation, interviews, documentation, and visual analysis of student activities in the learning process. Two types of interactive media, namely educational videos and technology-based games, were applied to measure the extent to which they were able to influence students' participation and numeracy literacy achievement. The results of the study showed a significant increase in the aspects of learning interest, active involvement, and students' understanding of numeracy concepts. Interactive media has been proven to provide a more enjoyable learning experience, facilitate practice-based learning, and increase student motivation in solving numeracy problems. In addition, teachers are also able to integrate interactive media into the curriculum without reducing the substance of the teaching material, so that this strategy serves as a complement to traditional learning methods. School support and the role of parents are also factors that determine the success of the implementation of these innovations. Theoretically, this research reinforces the relevance of constructivism and engagement theory in education, emphasizing the importance of the role of meaningful experiences and motivation in improving learning outcomes. As for practically, the findings of this study make a real contribution to teachers and education policymakers in developing numeracy learning strategies that are adaptive, creative, and in accordance with the demands of the 21st century.